Adaptasi Ikan Timpakul (Perioptholmodon schlosseri) di Habitat terganggu Muara Sungai Barito, Kalimantan Selatan: Adaptation of Timpakul fish (Perioptholmodon schlosseri) in disturbed habitat of Barito river estuary, South Kalimantan - Muhamat MUHAMAT; Heri Budi SANTOSO; Hidayaturrahmah HIDAYATURRAHMAH (Universitas Jambi, 2017)
Timpakul fish (Periophthalmodon schlosseri) is a kind of fish which able to live long in the land. One of the habitats of the fish is Barito river estuary. The development of land conversion which high enough at Barito river estuary into the area of fishponds and rice fields cause P. schlosseri must adapt to the environment disturbed. The research aimed to determine the adaptation of P. schlosseri in fishponds and rice fields habitats in Barito river estuary. The research is conducted by using the method of line transect, that is by walking in the area of rice fields and fishponds in Barito river estuary with the object of observation consisted of nest and activity of P. schlosseri. The results of observation showed that the density of P. schlosseri was relatively small at 0.54 individual/hectare in paddy fields areal and 0.84 individual/hectare the area of aquaculture. The relatively low density of fish was caused by nature solitary and carnivorous fish. The adaptation of P. schlosseri in the areas of fishponds and paddy fields could be successful because it was supported by adequate food source, that were crab, shrimp, frog and small fish and predators were relatively few. Keywords: Adaptation, Barito river estuary, disturbed habitat, Periophthalmodon schlosseri